Brand Affiliate sebagai Alternatif Membangun Brand Awareness - Trixie, Ivana; Pandrianto, Nigar (Prologia, 2024)
Technological developments, especially in social media platforms such as TikTok, have changed the marketing paradigm by focusing on dynamic consumer interactions. This research explores the impact of TikTok in building brand awareness, especially with the emergence of the concept of "Tiktok Affiliate." The research results show the important role of TikTok Affiliate in changing the digital marketing framework through creative content that effectively expands brand reach. Focusing on the brand case study "Somethinc" provides a unique contribution to the understanding of digital marketing and brand awareness in the TikTok era. The theoretical basis involves social media, TikTok, TikTok Affiliate, and brand awareness, with an emphasis on brand awareness indicators according to Keller. With innovative strategies, TikTok Affiliate is a key element in building brand awareness amidst contemporary digital marketing dynamics. The purpose of this research is to see how the Tiktok Affiliate brand is an alternative for building brand awareness for the Somethingnc brand. This research uses a qualitative approach with a case study method. The results of this research show that Tiktok Affiliate builds brand awareness through understanding Somehinc products. Creativity and authenticity in TikTok Affiliates content are key to attraction, creating a personal and authentic experience. Informative and compelling content helps consumers understand the product in depth, while direct interaction creates deeper engagement and builds a community around the brand. Perkembangan teknologi, khususnya di platform media sosial seperti TikTok, telah mengubah paradigma pemasaran dengan memfokuskan pada interaksi dinamis konsumen. Penelitian ini mengeksplorasi dampak TikTok dalam membangun brand awareness, khususnya dengan munculnya konsep "Tiktok Affiliate." Hasil penelitian menunjukkan peran penting TikTok Affiliate dalam mengubah kerangka kerja digital marketing melalui konten kreatif yang memperluas jangkauan brand secara efektif. Fokus pada studi kasus brand "Somethinc" memberikan kontribusi unik pada pemahaman digital marketing dan brand awareness di era TikTok. Landasan teori melibatkan media sosial, TikTok, TikTok Affiliate, dan brand awareness, dengan penekanan pada indikator brand awareness menurut Keller. Dengan strategi inovatif, TikTok Affiliate menjadi elemen kunci dalam membangun brand awareness di tengah dinamika pemasaran digital kontemporer. Tujuan penelitian ini untuk melihat bagaimana brand Tiktok Affiliate sebagai alternatif untuk membangun brand awareness pada brand Somethinc. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus. Hasil penelitian ini menunjukkan bahwa Tiktok Affiliate dalam membangun brand awareness melalui pemahaman produk Somethinc. Kreativitas dan keaslian dalam konten Tiktok Affiliates menjadi kunci daya tarik, menciptakan pengalaman personal dan autentik. Konten yang informatif dan meyakinkan membantu konsumen memahami produk secara mendalam, sementara interaksi langsung menciptakan keterlibatan yang lebih mendalam dan membangun komunitas di sekitar brand.